Dipper-like variability of the Gaia alerted young star V555 Ori. Issue 1 (27th March 2021) - Nagy, Zsófia; Szegedi-Elek, Elza; Ábrahám, Péter; Kóspál, Ágnes; Bódi, Attila; Bouvier, Jérôme; Kun, Mária; Moór, Attila; Cseh, Borbála; Farkas-Takács, Anikó; Hanyecz, Ottó; Hodgkin, Simon; et al.
ABSTRACT: V555 Ori is a T Tauri star, whose 1.5 mag brightening was published as a Gaia science alert in 2017. We carried out optical and near-infrared (NIR) photometric, and optical spectroscopic observations to understand the light variations. The light curves show that V555 Ori was faint before 2017, entered a high state for about a year, and returned to the faint state by mid-2018. In addition to the long-term flux evolution, quasi-periodic brightness oscillations were also evident, with a period of about 5 d. At optical wavelengths both the long-term and short-term variations exhibited colourless changes, while in the NIR they were consistent with changing extinction. We explain the brightness variations as the consequence of changing extinction. The object has a low accretion rate whose variation in itself would not be enough to reproduce the optical flux changes. This behaviour makes V555 Ori similar to the pre-main sequence star AA Tau, where the light changes are interpreted as periodic eclipses of the star by a rotating inner disc warp. The brightness maximum of V555 Ori was a moderately obscured ( AV = 2.3 mag) state, while the extinction in the low state was AV = 6.4 mag. We found that while the Gaia alert hinted at an accretion burst, V555 Ori is a standard dipper, similar to the prototype AA Tau. However, unlike in AA Tau, the periodic behaviour was also detectable in the faint phase, implying that the inner disc warp remained stable in both the high and low states of the system.